Job satisfaction among employee in Jaya Jusco Maluri / Mohd Aiman Mohammad Bohari (Faculty of Business Management, 2007)
This research was conducted for the purposed of "Job Satisfaction Among Employee in Jaya Jusco Maluri". The main objective of this research was to identify the factors that influence job satisfaction level among employee in Jaya Jusco Maluri The respondent of this study was employee of Jaya Jusco Maluri. 50 questionnaires had been distributed to the employee of Jaya Jusco Maluri. The researcher had used stratified simple random sampling as the sampling technique. The conclusion of this study was the outcome from the survey analysis and findings. Through the research, it shows that majority of the employee who work in Jaya Jusco Maluri achieve moderate job satisfaction level.